2019
DOI: 10.3389/fmars.2019.00583
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Phytoplankton Advection on the Productivity Along the Atlantic Water Inflow to the Arctic Ocean

Abstract: Northwards flowing Atlantic waters transport heat, nutrients, and organic carbon in the form of zooplankton into the eastern Greenland Sea and Fram Strait. Less is known of the contribution of phytoplankton advection in this current, the Atlantic Water Inflow (AWI) spanning from the North Atlantic to the Arctic Ocean. The in situ and advected primary production was estimated using the physical-biological coupled SINMOD model over a region bounded by northern Norway coast (along the Norwegian Atlantic Current, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 102 publications
(155 reference statements)
1
29
0
Order By: Relevance
“…No statistically significant responses to any of the supplied nutrient combinations relative to unamended controls were found in Experiments 3 and 4, located in the western and central Fram Straight respectively. This could either be a result of (i) limitation by an alternative resource (light or another nutrient); (ii) grazer regulation of the phytoplankton community, maintaining phytoplankton standing stocks despite enhanced specific growth rates following nutrient supply (e.g., Mann and Chisholm 64 ); or (iii) restricted net phytoplankton community growth over the experimental duration (72 h) due to low starting biomass concentrations and/or cold temperatures 65 . Our results do not allow us to unambiguously distinguish between these; however, ancillary observations allow identification of the most probable factors.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…No statistically significant responses to any of the supplied nutrient combinations relative to unamended controls were found in Experiments 3 and 4, located in the western and central Fram Straight respectively. This could either be a result of (i) limitation by an alternative resource (light or another nutrient); (ii) grazer regulation of the phytoplankton community, maintaining phytoplankton standing stocks despite enhanced specific growth rates following nutrient supply (e.g., Mann and Chisholm 64 ); or (iii) restricted net phytoplankton community growth over the experimental duration (72 h) due to low starting biomass concentrations and/or cold temperatures 65 . Our results do not allow us to unambiguously distinguish between these; however, ancillary observations allow identification of the most probable factors.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, some modelling suggests that decreasing sea-ice cover may lead to increased import of Atlantic Waters—and thus, fixed N—to the Fram Strait region 98 . Therefore in addition to changes in the areal extent of ice-free ocean 27 , 99 , 100 any future projection of primary production in the Fram Strait region is also hampered by poor knowledge of changes in nutrient supply as a result of the strong seasonal and inter-annual variability in current regimes 31 , 73 , changes in phytoplankton community composition and their nutrient requirements 57 , 65 , 101 . This compounds a poor mechanistic understanding of what drives elevated dFe and Si concentrations in the Transpolar Drift and how this will respond to future climate perturbations 19 , 45 , 75 .…”
Section: Resultsmentioning
confidence: 99%
“…In the future, an increase in the amount of bioavailable DOM could stimulate the competition for mineral nutrients between phytoplankton and bacteria [90], releasing more CO 2 during bacterial respiration. Therefore, future changes to BP might reduce the net community production in the microbial food web and weaken CO 2 sequestration in the Arctic [27]. As such, parameters characterizing microbial food web dynamics, including components within semi-labile DOM, are of importance if we aim to assess future carbon cycling in the changing Arctic ecosystem.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it needs to be supplemented and validated with a significant amount of in situ observations. This is all the more important that the recent studies revealed potential climate-generated changes in the productivity of the Atlantic-Arctic sector, including slight trends toward higher productivity in the eastern Fram Strait (Nöthig et al, 2015), a considerable influence of AW advected phytoplankton on the local in situ primary production (Vernet et al, 2019), and a shift in the summer months plankton composition from large diatoms toward Phaeocystis pouchetii and other small flagellates (e.g., Lalande et al, 2013;Nöthig et al, 2015).…”
Section: Introductionmentioning
confidence: 99%